Pengaruh Penggunaan Metode Pembelajaran Berbasis Game Adaptasi Clash Of Champions (COC) Terhadap Kemampuan Numerasi Siswa - Maghfirah Widiyati, Ayu; Wulandari, Rika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy is the ability to understand and apply mathematical concepts to aspects of life. Indonesia is one of the countries with low numeracy skills. A popular intelligence competition program in Indonesia is Clash of Champions (COC). The games in COC can be adapted into game-based learning methods to improve students' numeracy skills. This study aims to examine the effect of implementing a game-based learning method adapted from Clash of Champions (COC) on students' numeracy skills. This study uses a quantitative approach with a quasi-experimental design of the Pre-test-Post-test Non-equivalent Control Group Design. The research sample consisted of two classes determined by purposive sampling, namely VA students as the experimental class and VB students as the control class. The data collection technique used was testing through initial ability (pre-test) and final ability (post-test) instruments. The data analysis techniques used were homogeneity test, normality test, and hypothesis testing using the Independent Sample t-Test. Based on the results of the hypothesis test, it was found that there was no significant difference between